Combination Therapy with 1% Nanocurcumin Gel and 0.1% Triamcinolone Acetonide Mouth Rinse for Oral Lichen Planus: A Randomized Double-Blind Placebo Controlled Clinical Trial. (20th May 2020) - Bakhshi, Mahin; Gholami, Shahzad; Mahboubi, Arash; Jaafari, Mahmoud Reza; Namdari, Mahshid
Abstract : Objectives . This study aimed to evaluate the efficacy of a combination of 1% nanocurcumin gel with 0.1% triamcinolone acetonide mouth rinse for oral lichen planus (OLP). Materials and Methods . This double-blind randomized clinical trial was conducted on 31 patients with erosive or ulcerative OLP. All patients received 0.1% triamcinolone mouth rinse and were then randomly divided into two groups for combination therapy with (I) %1 nanocurcumin gel or (II) placebo gel. The reticular-erosive-ulcerative (REU) score was calculated at baseline and at two and four weeks after the intervention. The changes in the mean REU score and the efficacy index were calculated to determine the level of improvement after two and four weeks. Data were analyzed using independent t -test, repeated measures ANCOVA, Mann–Whitney test, and chi-square test. P < 0.05 was considered statistically significant. Results . There were 14 patients in the nanocurcumin and 17 patients in the placebo group. A significantly higher decrease in the mean REU score was observed in the nanocurcumin compared with the placebo group (P < 0.001 ). The efficacy index was significantly higher in the nanocurcumin group (P < 0.001 ). Conclusion . Application of 1% nanocurcumin in combination with 0.1% triamcinolone acetonide can serve as an effective treatment strategy to enhance the level of improvement of lesions compared with the use of triamcinolone acetonide alone.